Early Pregnancy Complications and Risk Factors (Medical Forum Monthly, 2024)
Objective: To determine the underlying risk factors in early pregnancy complication and outcome.Study design: Case series study.Place and duration of Study: This study was conducted in the Department of Obstetrics & Gynaecology at Peoples Medical College Hospital Nawabshah from January 2010 to December 2010.Materials and Methods: All the women with first trimester pregnancy with different complications were included in this study, while those women with uneventful first trimester were excluded. The included women were registered on pre-designed proforma studied variable including demographic details, gestational period, type of complication, risk factor treatment and outcome. The data was examined in terms of mean and percentage with a confidence interval of 95 %. Analysis was done on SPSS version 10.Results: Out of 661 total early pregnancy admissions, 309 (46 – 74 %) patients had different early pregnancy of complication. Their mean age was 29.22 ± 6.22 years. Commonest complications found were abortion in 206 (66.66 %) cases. The underlying risk factors found in miscarriage were antiphospholipid syndrome in 8 (3.88 %) cases, diabetes mellitus in 35 (16.99 %) cases. Hypertension in 50 (24.27 %) cases, PCOS in 15 (7.28 %) cases and infection in 10 (4.85 %) cases.60 (61.22 %) cases were treated by minor surgical procedures and 38 (38.77 %) cases treated with conservative medical therapy. Outcome were anaemia in 245 (79.28 %) cases, psychological upset in 189 (61.16 %), infection in 131 (42.39 %) and coagulopathy in 17 (5.50%) cases.Conclusion: Miscarriage was found as the most frequent early pregnancy complication and the most frequent risk factor was hypertension. Outcome included anaemia, psychological upset and infection.